2003
DOI: 10.1002/joc.948
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variations of storm tracks in the Southern Hemisphere and their connections with the Antarctic oscillation

Abstract: Interannual variations of storm tracks in the Southern Hemisphere (SH) are studied. Large interannual variations are found in the enveloping function of meridional wind v e and these suggest some dominant periodicities. Some of these periodicities are a quasi-biennial oscillation in the subtropical branch of the winter storm track and the midlatitude spring storm track, a 3 year period and a long period of 8 years. The Antarctic oscillation (AAO) seems to be connected to the interannual variation of storm trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The changing SAM has also been associated with observed changes in Southern Hemisphere rainfall (Brahmananda Rao et al, 2003), surface and sea surface temperatures (Mo 2000;Hall & Visbeck, 2002;Screen et al, 2009), Antarctic sea ice extent and concentration (Lefebvre et al, 2004;Liu et al, 2004), variability of storm tracks (Brahmananda Rao et al, 2003;Yin 2005;Lubin et al, 2008), oceanic circulation (Hall & Visbeck 2002;Sen Gupta & England 2006;Russell et al, 2006), and carbon dioxide (and heat) exchanges between the atmosphere and the ocean (Mignone et al, 2006). Gillet et al (2006) S. This is in agreement with other modelling studies (Watterson, 2000;Cai & Watterson, 2002;Sen Gupta & England, 2006) which have also shown significant warming trends (across the Southern Ocean) associated with the positive phase of the SAM.…”
Section: The Circumpolar Vortex and The Southern Annular Modementioning
confidence: 90%
“…The changing SAM has also been associated with observed changes in Southern Hemisphere rainfall (Brahmananda Rao et al, 2003), surface and sea surface temperatures (Mo 2000;Hall & Visbeck, 2002;Screen et al, 2009), Antarctic sea ice extent and concentration (Lefebvre et al, 2004;Liu et al, 2004), variability of storm tracks (Brahmananda Rao et al, 2003;Yin 2005;Lubin et al, 2008), oceanic circulation (Hall & Visbeck 2002;Sen Gupta & England 2006;Russell et al, 2006), and carbon dioxide (and heat) exchanges between the atmosphere and the ocean (Mignone et al, 2006). Gillet et al (2006) S. This is in agreement with other modelling studies (Watterson, 2000;Cai & Watterson, 2002;Sen Gupta & England, 2006) which have also shown significant warming trends (across the Southern Ocean) associated with the positive phase of the SAM.…”
Section: The Circumpolar Vortex and The Southern Annular Modementioning
confidence: 90%
“…These changes in zonal wind are again characteristic of the increased MSLP gradient between mid-and high latitudes linked to the SAM (Thompson and Wallace 2000;Hall and Visbeck 2002). Associations between the SAM and extratropical storm tracks, as described by Rao et al (2003), and observed and projected poleward shifts in the position of the storm tracks under a more positive SAM phase (Fyfe 2003;Yin 2005) could account for the reduced rainfall across the South Island during dry years. Dry (wet) years also coincide with more southerly (northerly) wind anomalies across New Zealand, and especially over a region to the northeast of the country (Figs.…”
mentioning
confidence: 86%
“…At the same time the Antarctic Peninsula warms as a result of fewer cold air outbreaks from the continent and intensified advection of warm air from the ocean. The influence of the SAM has also been identified in moisture transport and precipitation (Boer et al 2001), storm track activity and regional rainfall (Brahmananda Rao et al 2003), sea surface temperature (Mo 2000;Hall and Visbeck 2002;Screen et al 2009), ocean circulation (Hall and Visbeck 2002;Sen Gupta and England 2006, hereafter referred to as SGE06), and sea ice concentration (Lefebvre et al 2004;Liu et al 2004).…”
Section: Introductionmentioning
confidence: 99%